Lithospheric Removal Beneath the Eastern Flank of the Rio Grande Rift From Receiver Function Velocity Analysis. (15th February 2019) - Agrawal, Mohit; Pulliam, Jay; Sen, Mrinal K.; Grand, Stephen P.
Abstract: We develop and apply a technique for receiver functions that is analogous to "velocity analysis" in seismic reflection processing, in which a velocity model is found directly from the data. In the case of receiver functions, which represent waves converted from P type to S type ( Ps ) or S type to P type ( Sp ) rather than reflected waves, we jointly optimize the average correlation value for target features in common receiver gathers while perturbing shear wave velocities and Poisson's ratio in a process driven by simulated annealing. The technique simultaneously finds depths to major discontinuities and 1‐D S velocity profiles beneath each seismic station. Estimates of Poisson's ratio are used with S velocity models to estimate P velocities, and individual 1‐D profiles are interpolated to form a 3‐D velocity model. We stacked and depth migrated Ps and Sp receiver functions computed from data recorded by broadband stations in southeastern New Mexico and west Texas. Images reveal an abrupt increase in lithospheric thickness beneath the Great Plains craton with respect to the Rio Grande Rift. Ps results show that the Moho ranges from 36 to 60 km in the region, while Sp results show variations in the seismically determined lithosphere‐asthenosphere boundary of 75–112 km. Thickened crust and lithosphere overlie a high‐velocity anomaly determined previously via tomography. We speculate that the thickened crust and lithosphere maybe due to removal of the lower lithosphere by a process that is associated with east‐west extension and thus the northward propagation of the Rio Grande Rift. Key Points: We develop and apply a technique for receiver functions that is analogous to "velocity analysis" in seismic reflection processing The technique simultaneously finds depths to major discontinuities and S velocity profiles beneath each seismic station We speculate that thickened lithosphere maybe due to removal of lower lithosphere by a process that is associated with east‐west extension